Hak Asasi Manusia dalam Al-Qur’an (Fenomena Kekerasan Anak dan Konsep Perlindungannya dalam Al-Qur’an): Human Rights in the Qur'an (the Phenomenon of Child Abuse and the Concept of Protection in the Qur'an) - Ramdani, Fauziah; Achmad Abubakar; Aisyah Arsyad (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2024)
As creatures of Allah Swt. who are endowed with reason, humans are special creatures. His existence on earth with various roles and participation carried out as a form of implementation of the caliphate on this earth shows that humans are noble creatures. This research aims to describe the concept of human rights for children, both the concept of human rights in general and how the Qur'an reviews the issue of human rights, especially child protection in the Qur'an. The research method used is a qualitative approach with library research, reviewing books, journals and other references related to child protection in the perspective of the Qur'an. Child protection is a multitude attitude that must be given along with the increasing number of human rights violations committed both physically, sexually and psychologically in children.Keyword: Protection. Child, Violence, Human Rights, Qur'an. The number of 3,457 cases of child abuse shows that crimes against children are still not a major concern in the domestic sphere of the nuclear family, society and the state. Islam as a perfect religion, has clearly illustrated that the presence of children is a great gift that should be guarded and maintained properly. The protection of children can be found in several verses that establish the rights of children, such as the right to life (QS. Al-An'am: 151), the right to earn a living (QS. Al-Baqarah: 233), the right to be protected and get education (QS. Attahrim: 6).